Silencing a key gene of the common symbiosis pathway in Nicotiana attenuata specifically impairs arbuscular mycorrhizal infection without influencing the root‐associated microbiome or plant growth. (7th July 2015) - Groten, Karin; Nawaz, Ali; Nguyen, Nam H. T.; Santhanam, Rakesh; Baldwin, Ian T.
Abstract: While the biochemical function of calcium and calmodulin‐dependent protein kinase (CCaMK) is well studied, and plants impaired in the expression of CCaMK are known not to be infected by arbuscular mycorrhizal fungi (AMF) in glasshouse studies, the whole‐plant and ecological consequences of CCaMK silencing are not well understood. Here we show that three independently transformed lines of N icotiana attenuata plants silenced in CCaMK (ir CCaMK ) are neither infected by R hizophagus irregularis in the glasshouse nor by native fungal inoculum in the field. The overall fungal community of field‐grown roots did not differ significantly among empty vector (EV) and the transgenic lines, and the bacterial communities only showed minor differences, as revealed by the alpha‐diversity parameters of bacterial OTUs, which were higher in EV plants compared with two of the three transformed lines, while beta‐diversity parameters did not differ. Furthermore, growth and fitness parameters were similar in the glasshouse and field. Herbivory‐inducible and basal levels of salicylic acid, jasmonic acid and abscisic acid did not differ among the genotypes, suggesting that activation of the classical defence pathways are not affected by CCaMK silencing. Based on these results, we conclude that silencing of CCaMK has few, if any, non‐target effects. Abstract : While the biochemical function of calcium and calmodulin‐dependent protein kinase (CCaMK) is well studied, and plants impaired in the expression of CCaMK are known not to be infected by arbuscular mycorrhizal fungi (AMF), the whole‐plant and ecological consequences of CCaMK silencing are not well understood. Here we show that growth and fitness of three independently transformed lines of Nicotiana attenuata plants silenced in CCaMK (ir CCaMK ) and empty vector (EV) plants were similar in the glasshouse and the field. Except for AMF colonization, the overall fungal community of field‐grown roots did not differ significantly among empty vector and the transgenic lines, and the bacterial communities only showed minor differences. Based on these results we conclude that silencing of CCaMK has few, if any, non‐target effects.